PENINGKATAN HASIL BELAJAR MATEMATIKA MATERI VOLUME KUBUS DAN BALOK MELALUI PENERAPAN METODE MIND MAP PADA SISWA KELAS VI-B SD NEGERI JAJAR TUNGGAL III SURABAYA - Munif Fatul Asiyah; Ulhaq Zuhdi; Galuh Guminar Asmoro (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This classroom action research aims to improve student learning outcomes in the Mathematics subject material volume of cubes and blocks by using the Mind map method or concept map which consists of four stages, namely planning, action or actions, observation and reflection. This classroom action research was carried out in class VI-B of SD Negeri Jajar Tunggal III Surabaya involving 28 students. The data collection instruments used were observation and learning outcomes tests. The results of the research showed that there was an increase in the learning outcomes of class VI-B students at SD Negeri Jajar Tunggal III Surabaya in the mathematics subject material Volume of cubes and blocks as evidenced by the first cycle of students achieving a KKM of 57.2% with an average score of 68 and more. again in cycle II with a percentage of 89.3% with an average value of 87.5. From these results it can be shown that the application of the Mind map method is very effective in improving the learning outcomes of class VI-B students at SD Negeri Jajar Tunggal III Surabaya in the mathematics subject material Volume of cubes and blocks